Native-immigrant Wage Differentials in Malaysia - Borhan Abdullah; Ioannis Theodossiou; Alexandros Zangelidis (2020)
This paper utilizes Productivity and Investment Climate Survey (PICS)2007 data to explore native and immigrant wage differentials in Malaysia.An Oaxaca decomposition analysis was conducted by adapting Oaxaca and Ransom (1994)and Fortin’s(2008)approach using quantile regression to identify the non-discriminatory wage structure and the components of the wage differentials along theincome distribution.The findings of the study suggest that most of the native-immigrant wage gap can be explained by differences in endowments.This study also shows discrimination contributes to the wage gap by increasing the native wage by 15.4%above the non-discriminatory wage structure and reducing the immigrant wage by 13.3%.